Classroom Observation in the Bhutanese Classroom: Its Reality and Limitation - Tshewang (European Journal of Volunteering and Community-Based Projects)
Teaching-learning process in a classroom is best understood through classroom observation. Classroom observation helps teachers to improve their teaching-learning quality. The purpose of the study was to observe how teaching-learning process inside the classroom.  The study was qualitative in nature and used two rounds of classroom observations.  Data were collected from 35 (20 male and 15 female) teacher participants in the school. The study was conducted at one higher secondary school under Thimphu Thormde, Bhutan. A non-probability convenient sampling technique was used for the study. The classroom observation data were analyzed using the process of emerging themes. The finding of the study revealed that teaching consists of chalk and talk method and of teacher direct. Few students were found participating, involving, and questioning. A majority of teachers use lower order thinking questions with few teaching-learning materials. Lesson plans do not address all components of the teaching-learning process. The findings recommend ensuring teaching-learning materials such as models, toys, and visual tools in the classrooms. There is a frequent need for professional development on content and pedagogical practices for teachers to raise the quality of teaching-learning. Teachers need to maintain a standard lesson plan with various components of lesson introducing, the procedure of carrying out activities, explaining concepts, ways of assessing learning, and student engagement techniques.